1991
DOI: 10.1590/s0036-46651991000400003
|View full text |Cite
|
Sign up to set email alerts
|

Roedores silvestres como modelos experimentais da esquistossomose mansônica: Akodon arviculoides (Rodentia: Cricetidae)

Abstract: A infecção experimental do A. arviculoides através de diferentes vias de penetração das cercárias de Schistosoma mansoni (transcutânea e subeutânea) foi estudada pela cinética de eliminação de ovos nas fezes, pela recuperação dos vermes adultos (no sistema porta e nos vasos mesentéricos) e pelo oograma quantitativo. Demonstrou-se que a infecção do A. arviculoides assemelha-se à dos camundongos albinos que serviram de controle, quanto a eficácia das vias de penetração, ao habitat dos vermes adultos e ao oograma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0
3

Year Published

1993
1993
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 8 publications
3
12
0
3
Order By: Relevance
“…In our study, all infected groups had higher numbers of immature eggs in the distal small intestine, which corroborates other studies (Costa & Katz 1982, Machado e Silva et al 1991, Martinez et al 2003. Adult PR offspring had a higher total number of eggs in their faeces and intestinal portions, as well as a higher number of eggs in all stages of development.…”
Section: Table IVsupporting
confidence: 93%
See 1 more Smart Citation
“…In our study, all infected groups had higher numbers of immature eggs in the distal small intestine, which corroborates other studies (Costa & Katz 1982, Machado e Silva et al 1991, Martinez et al 2003. Adult PR offspring had a higher total number of eggs in their faeces and intestinal portions, as well as a higher number of eggs in all stages of development.…”
Section: Table IVsupporting
confidence: 93%
“…removed (Machado e Silva et al 1991). Segments were opened, washed and crushed between two glass slides to obtain a thin preparation.…”
Section: Methodsmentioning
confidence: 99%
“…It is well established that in well-fed mice, S. mansoni eggs are trapped mainly in the small intestine (Nyndo & Farah 1999). In this regard, about 50% of the eggs lodge in the distal segment of the small intestine (Costa & Katz 1982, Machado-Silva et al 1991. Meanwhile, our results showed that malnourished mice had a higher egg count in the proximal segment.…”
Section: Discussionmentioning
confidence: 57%
“…From each segment a sample (1 cm long) was obtained. A same procedure was taken for colon segment (Machado-Silva et al 1991). All fragments were crushed between two glass slides.…”
Section: Methodsmentioning
confidence: 99%
“…For this reason, some species of wild rodents have been introduced for captive conditions and were employed as natural-hosts animal models for schistosomiasis studies (Machado e Silva et al 1991, Maldonado Jr. et al 1994, Lenzi et al 1995, Ribeiro et al 1998.…”
Section: Introductionmentioning
confidence: 99%